1H NMR technique for kinetic investigation of equilibrium between the Z- and E-isomers in a stable phosphorus ylide involving a 2-indolinone. (7th July 2012) - Khorassani, Sayyed Mostafa Habibi; Maghsoodlou, Malek Taher; Aghdaei, Elham; Shahraki, Mehdi
For the first time, a kinetic investigation of the interchange process in the equilibrium between the Z- and E-isomers of a stable phosphorus ylide involving a 2-indolinone has been undertaken by the 1H NMR technique. Activation parameters such as k–1, k1, ktotal, Ea1, Ea–1, Eatotal, ΔS≠, ΔH≠ and ΔG≠ along with thermodynamic parameters such as Ke, ΔH°, ΔG° and ΔS° were obtained from experimental data for the forward and reverse reactions.